Development of E-Booklet on Ethnobotany-Based Diversity of Living Creatures in Colo Village, Gunung Muria - Nurul Inayah; Margareta Rahayuningsih (Universitas Negeri Semarang, 2025)
The ethnobotany of Colo Village is important local wisdom that should be preserved, including through an e-booklet on the Diversity of Living Organisms. This study analyzes biodiversity based on ethnobotany and evaluates the feasibility and readability of the e-booklet using the Research and Development (R&D) method with the 4D model. The results identify genetic, species, and ecosystem diversity. Genetic diversity is observed in the color variations of paper flowers (Zinnia elegans L.), roses (Rosa hybrida), and ixora flowers (Ixora coccinea L.). Species diversity includes 39 plant species from 28 families, while ecosystem diversity consists of forests, coffee plantations, and residential areas. Validation by material experts shows content feasibility at 77%, presentation 80%, and contextual assessment 77%. Media experts rate graphics at 99% and language at 100%. Teachers from SMAN 1 Mijen Demak assess usefulness at 73%, ease of use and appearance at 84%, and attractiveness at 79%, while SMAN 1 Kudus teachers rate these aspects at 95%, 100%, 100%, and 95%. Student response tests from SMAN 1 Mijen Demak show 83% for usefulness, 81% for ease of use, 83% for appearance, and 80% for attractiveness. SMAN 1 Kudus students rate these aspects at 83%, 86%, 81%, and 78%. Cloze test results show 88% for SMAN 1 Mijen Demak and 94% for SMAN 1 Kudus. The e-booklet is deemed feasible and highly readable.